Composite functional filler with heat-conducting and anti-corrosion effects as well as preparation method and application of composite functional filler
The boron nitride is physically coated and modified by the silicone sol modified by the rust converter, which solves the problems of uneven dispersion of boron nitride fillers in the coating and the harsh storage conditions, and achieves uniform dispersion of the composite functional fillers and good corrosion resistance and thermal conductivity.
Patent Information
- Application Number
- CN202411548824.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-25
AI Technical Summary
Existing boron nitride fillers are prone to clusters when used in coatings, resulting in uneven dispersion, and specific technologies and equipment are required to ensure uniformity and adhesion of the coating. Storage conditions are harsh, and traditional modification methods are complex and costly.
The hexagonal boron nitride is physically coated and modified by a silicon sol modified with a rust converter. The modified silicon sol is formed by the condensation reaction of gallic acid and the silicon sol, and then mixed with boron nitride, dispersed by ball mill and sieved to obtain a composite functional filler with a particle size of 200 mesh to 400 mesh.
The uniform dispersion and good adhesion of boron nitride filler are achieved, the coating construction process is simplified, the corrosion resistance and thermal conductivity of the coating are improved, and the production cost and environmental impact are reduced.
Smart Images

Figure CN119505595A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a composite functional filler, in particular to a composite functional filler having both heat conduction and anti-corrosion effects, and also to a preparation method and application of the composite functional filler. Background Art
[0002] The special functions of fillers in coatings mainly include the following aspects: skeleton and filling effect; adjusting rheological properties; improving mechanical strength; adjusting optical properties; improving water resistance and weather resistance; chemical properties auxiliary; reducing costs; improving the construction performance of coatings; improving the hardness, mechanical strength, hiding power, weather resistance, water resistance, solvent resistance, bending resistance, scratch resistance and crack resistance of the coating film; adjusting color and providing special effects; and there are other functional filler applications, such as fireproofing, waterproofing, antibacterial, antistatic, etc.
[0003] Hexagonal boron nitride is a high-end functional inorganic filler with a typical two-dimensional structure and unique physical and chemical properties. When doped in coatings, it can make the coatings have good high-temperature stability, wear resistance, corrosion resistance, thermal conductivity, electrical insulation, lubricity, non-wetting and other characteristics. It can be used in heat resistance, corrosion resistance and other fields; however, due to the surface passivation characteristics and poor wettability of boron nitride, it is easy to cluster when dispersed in the coating system. In addition, the application of boron nitride coatings may require specific technology and equipment to ensure the uniformity and adhesion of the coating, and the coatings added with boron nitride need to be stored under specific temperature and humidity conditions to maintain their performance. Therefore, boron nitride needs to be modified by stripping or surface modification to optimize its application in coatings. However, traditional modification methods are relatively complicated and costly, and it is urgent to study new composite functional fillers and develop efficient, convenient and practical preparation methods. Summary of the invention
[0004] Purpose of the invention: The purpose of the present invention is to provide a composite functional filler having both thermal conductivity and anti-corrosion effects, and also to provide a preparation method and application of the above-mentioned composite functional filler.
[0005] Technical solution: The present invention discloses a composite functional filler having both thermal conductivity and anti-corrosion effects. The composite functional filler is based on boron nitride, and its surface is physically coated and modified with silica sol modified by a rust conversion agent.
[0006] Wherein, the rust conversion agent is gallic acid, and the boron nitride is hexagonal boron nitride.
[0007] The composite functional filler has a rough surface and a particle size of 200-400 meshes.
[0008] The method for preparing the composite functional filler comprises the following steps:
[0009] (1) dissolving gallic acid in an ethanol solvent, then adding the gallic acid to the silica sol, and after being evenly dispersed, adding a catalyst, and reacting the carboxyl groups on the gallic acid with the hydroxyl groups on the silica sol for condensation esterification, stirring at a speed of 400 to 800 rpm, heating to 50 to 70° C., and reacting for 4 to 8 hours to obtain an intermediate product I;
[0010] (2) first adding a wetting dispersant to anhydrous ethanol, then adding hexagonal boron nitride powder, and ultrasonically dispersing it for 4 to 6 hours using an ultrasonic disperser to fully disperse it to obtain an intermediate product II;
[0011] (3) mixing the intermediate product I with the intermediate product II, and stirring at a rotation speed of 200 to 1000 rpm at room temperature for 0.5 to 5 hours to obtain a mixture;
[0012] (4) placing the mixture in a rotary evaporator, heating it to 40°C to 60°C at 0.05 to 0.2 atmospheres, reacting it for 0.5 to 2 hours to remove the solvent, and dispersing the obtained product through ball milling, and sieving it to obtain a composite filler with a particle size of 200 mesh to 400 mesh.
[0013] Wherein, in step (1), the concentration of gallic acid in ethanol is 0.5-5 g / ml; the silica sol has a solid content of 30%, a particle size of 10-20 nm, and a pH value of 7-10.
[0014] Wherein, in step (1), the catalyst is dimethylamino arsenic.
[0015] Wherein, in step (2), the wetting and dispersing agent is an anionic wetting and dispersing agent, which may be a sulfate ester salt, a sulfonate ester salt, sodium oleate, a carboxylate, or the like.
[0016] Wherein, in step (2), the particle size range of the hexagonal boron nitride is 5 to 30 microns.
[0017] Wherein, in step (2), the concentration of boron nitride dispersed in anhydrous ethanol is 25-100 g / l, the ultrasonic frequency of the ultrasonic disperser is 40 kHz, and the power range is 50-900 W.
[0018] Wherein, in step (3), the mass ratio of intermediate product I to intermediate product II is 100:1 to 10:1.
[0019] The above-mentioned composite functional filler can also be used in the field of coating protection.
[0020] The coating is prepared by mixing the composite functional filler, epoxy resin, polyamide curing agent 651, xylene, defoaming agent, leveling agent and wetting dispersant.
[0021] Principle of the invention: The composite functional filler of the present invention adopts silica sol modified by rust conversion agent to wrap boron nitride. Since the silica sol component has good adhesion, strong adhesion, good permeability and good dispersibility, it can effectively physically coat the surface of the boron nitride filler, and can be used to adsorb rust conversion agents such as gallic acid while improving the surface wettability of the filler. While improving the uniform dispersion effect of the composite filler in the coating system, due to the rust conversion effect of gallic acid, the processing and construction process of the substrate is simplified, and the corrosion resistance of the coating is further improved.
[0022] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The composite functional filler of the present invention has excellent thermal conductivity and rust prevention effects, and has thermal conductivity and corrosion resistance when applied to composite coatings; (2) The composite functional filler of the present invention is obtained by surface modification of boron nitride by physical blending, which has a simple operation process, is environmentally friendly, does not cause harm, and has significant economic and environmental benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a scanning electron microscope image of the composite functional filler having both heat conduction and rust prevention effects of the present invention;
[0024] Figure 2 The scanning electron microscope image of the cross-sectional morphology of the epoxy composite coating prepared by the composite functional filler of the present invention;
[0025] Figure 3 A schematic diagram comparing the thermal conductivity of an epoxy composite coating made of a composite functional filler and a coating made of hexagonal boron nitride in Example 1 of the present invention;
[0026] Figure 4 This is a schematic diagram showing the comparison between the epoxy composite coating made of the composite functional filler in Example 1 of the present invention and the coating made of ordinary hexagonal boron nitride after salt spray corrosion. DETAILED DESCRIPTION
[0027] The technical scheme of the present invention is further described below in conjunction with the examples. The test materials used in the examples can all be purchased through conventional channels.
[0028] Example 1
[0029] The composite functional filler with both heat conduction and anti-corrosion effects of the present invention comprises the following steps:
[0030] (1) dissolving gallic acid in an ethanol solvent, wherein the concentration of gallic acid in the ethanol is controlled to be 0.5 g / ml, and then adding the solution to a silica sol having a solid content of 30%, a particle size of 10 nm, and a pH value of 10. After the solution is evenly dispersed, a catalyst is added, wherein the catalyst is dimethylaminopyridine, and a condensation esterification reaction is carried out. The mixture is stirred at a speed of 400 rpm, heated to 70° C., and reacted for 4 hours to obtain an intermediate product I;
[0031] (2) firstly adding a wetting and dispersing agent into anhydrous ethanol, wherein the wetting and dispersing agent is an anionic wetting and dispersing agent of a sulfate ester salt, and then adding hexagonal boron nitride powder, wherein the particle size of the hexagonal boron nitride is 5 μm, and the concentration of the boron nitride dispersed in anhydrous ethanol is 100 g / l, and then ultrasonically dispersing the hexagonal boron nitride for 4 hours in an ultrasonic disperser, wherein the ultrasonic frequency of the ultrasonic disperser is 40 kHz and the power range is 900 W, so that the hexagonal boron nitride powder is fully dispersed and uniformly dispersed to obtain an intermediate product II;
[0032] (3) mixing the intermediate product I and the intermediate product II in a mass ratio of 10:1, stirring at a speed of 200 rpm at room temperature for 5 hours to obtain a mixture;
[0033] (4) The mixture was placed in a rotary evaporator, heated to 60° C. at 0.05 atmospheric pressure, and reacted for 0.5 hours to remove the solvent. The obtained product was dispersed by ball milling and sieved to obtain a composite functional filler with a particle size of 400 mesh.
[0034] Example 2
[0035] The composite functional filler with both heat conduction and anti-corrosion effects of the present invention comprises the following steps:
[0036] (1) dissolving gallic acid in an ethanol solvent, wherein the concentration of gallic acid in the ethanol is controlled to be 1 g / ml, and then adding the solution to a silica sol having a solid content of 30%, a particle size of 15 nm, and a pH value of 8. After being uniformly dispersed, a catalyst is added, wherein the catalyst is dimethylaminopyridine, and a condensation esterification reaction is carried out. The mixture is stirred at a speed of 500 rpm, heated to 60° C., and reacted for 5 hours to obtain an intermediate product I;
[0037] (2) firstly adding a wetting and dispersing agent into anhydrous ethanol, wherein the wetting and dispersing agent is an anionic wetting and dispersing agent of sulfonate salt, and then adding hexagonal boron nitride powder, wherein the particle size of hexagonal boron nitride is 10 μm, and the concentration of boron nitride dispersed in anhydrous ethanol is 80 g / l, and then ultrasonically dispersing the powder for 4.5 hours in an ultrasonic disperser, wherein the ultrasonic frequency of the ultrasonic disperser is 40 kHz and the power range is 500 W, so that the powder is fully dispersed and uniformly distributed, thereby obtaining an intermediate product II;
[0038] (3) mixing the intermediate product I and the intermediate product II in a mass ratio of 30:1, stirring at a speed of 400 rpm at room temperature for 4 hours to obtain a mixture;
[0039] (4) The mixture was placed in a rotary evaporator, heated to 55° C. at 0.08 atmospheric pressure, and reacted for 1 hour to remove the solvent. The obtained product was dispersed by ball milling and sieved to obtain a composite functional filler with a particle size of 300 mesh.
[0040] Example 3
[0041] The composite functional filler with both heat conduction and anti-corrosion effects of the present invention comprises the following steps:
[0042] (1) dissolving gallic acid in an ethanol solvent, wherein the concentration of gallic acid in the ethanol is controlled to be 3 g / ml, and then adding the solution to a silica sol having a solid content of 30%, a particle size of 18 nm, and a pH value of 9. After the solution is evenly dispersed, a catalyst is added, wherein the catalyst is dimethylaminopyridine, and a condensation esterification reaction is carried out. The mixture is stirred at a speed of 600 rpm, heated to 55° C., and reacted for 7 hours to obtain an intermediate product I.
[0043] (2) firstly adding a wetting and dispersing agent into anhydrous ethanol, wherein the wetting and dispersing agent is an anionic wetting and dispersing agent of sodium oleate, and then adding hexagonal boron nitride powder, wherein the particle size of hexagonal boron nitride is 20 μm, and the concentration of boron nitride dispersed in anhydrous ethanol is 50 g / l, and then ultrasonically dispersing the powder for 5 hours in an ultrasonic disperser, wherein the ultrasonic frequency of the ultrasonic disperser is 40 kHz and the power range is 300 W, so that the powder is fully dispersed and uniformly distributed, thereby obtaining an intermediate product II;
[0044] (3) mixing the intermediate product I and the intermediate product II in a mass ratio of 50:1, stirring at 600 rpm at room temperature for 2 hours to obtain a mixture;
[0045] (4) The mixture was placed in a rotary evaporator, heated to 45° C. at 0.15 atmospheric pressure, and reacted for 1.5 hours to remove the solvent. The obtained product was dispersed by ball milling and sieved to obtain a composite functional filler with a particle size of 250 mesh.
[0046] Example 4
[0047] The composite functional filler with both heat conduction and anti-corrosion effects of the present invention comprises the following steps:
[0048] (1) dissolving gallic acid in an ethanol solvent, wherein the concentration of gallic acid in the ethanol is controlled to be 5 g / ml, and then adding the solution to a silica sol having a solid content of 30%, a particle size of 20 nm, and a pH value of 7. After the solution is evenly dispersed, a catalyst is added, wherein the catalyst is dimethylaminopyridine, and a condensation esterification reaction is carried out. The mixture is stirred at a speed of 800 rpm, heated to 50° C., and reacted for 8 hours to obtain an intermediate product I.
[0049] (2) firstly adding a wetting and dispersing agent into anhydrous ethanol, wherein the wetting and dispersing agent is an anionic wetting and dispersing agent of carboxylate, and then adding hexagonal boron nitride powder, wherein the particle size of hexagonal boron nitride is 30 μm, and the concentration of boron nitride dispersed in anhydrous ethanol is 20 g / l, and then ultrasonically dispersing the powder for 6 hours in an ultrasonic disperser, wherein the ultrasonic frequency of the ultrasonic disperser is 40 kHz and the power range is 50 W, so that the powder is fully dispersed and uniformly distributed, thereby obtaining an intermediate product II;
[0050] (3) mixing the intermediate product I and the intermediate product II in a mass ratio of 100:1, stirring at 1000 rpm at room temperature for 0.5 hour to obtain a mixture;
[0051] (4) The mixture was placed in a rotary evaporator, heated to 40° C. at 0.2 atmospheres, and reacted for 2 hours to remove the solvent. The obtained product was dispersed by ball milling and sieved to obtain a composite functional filler with a particle size of 200 mesh.
[0052] The composite functional fillers prepared in Examples 1 to 4 were used, and according to the raw material ratios shown in Table 1, coatings doped with the composite functional fillers prepared in the present invention having both thermal conductivity and hydrophobicity were prepared.
[0053] Table 1. Paint preparation scheme of composite fillers prepared according to the present invention
[0054]
[0055] The defoamers are BYK-070 and BYK-8800 from BYK, or BYK-100 from Digo. Foamex N. The leveling agent may be BYK-333 produced by BYK. The wetting and dispersing agent may be A-5088 or A-5044 produced by FKA.
[0056] The preparation scheme is as follows: first, add epoxy resin and wetting dispersant to half of xylene, stir at a high speed of 1000 rpm for 5 minutes, and stir evenly. Then gradually add the composite filler prepared by the present invention, stir at a high speed of 1200 rpm for 1 hour, and then add the leveling agent, defoamer and remaining xylene solvent. Stir at 500 rpm for 15 minutes and mix evenly. Before coating the plate, add the polyamide curing agent 651 shown in Table 1, stir evenly to obtain the designed composite coating, and each coating is correspondingly defined as Example 1 coating, Example 2 coating, Example 3 coating, and Example 4 coating. It is applied to the surface of the metal substrate by brushing, spraying or rolling, and is left at room temperature for 7 days to form an epoxy composite coating and test its various properties.
[0057] Take the hexagonal boron nitride powder with a particle size of 5 microns used in Example 1, replace the composite filler with both thermal conductivity and anti-corrosion effects prepared in Examples 1 to 4 in Table 1, and carry out the above preparation. The obtained coating is recorded as the comparative example 1 coating, which is applied to the surface of the metal substrate and left at room temperature for 7 days to form a coating and its various properties are tested.
[0058] The specific performance indicators of the coating prepared based on the composite filler prepared by the present invention and the coating prepared by the comparative example coating are shown in Table 2 below:
[0059] Table 2. Performance indicators of composite coatings and their cured coatings
[0060]
[0061]
[0062] Figure 1 The overall morphology of the composite functional filler with both thermal conductivity and anti-corrosion effects prepared in Example 1 observed by scanning electron microscopy. It can be seen that the filler formed after the hexagonal boron nitride is coated and modified has a rough and uneven surface, which is conducive to promoting the effective dispersion of the filler in the resin.
[0063] Figure 2 The cross-sectional morphology of the epoxy composite coating formed by coating the coating prepared by the composite functional filler doped in Example 1 by scanning electron microscopy is shown. Due to the modification of the filler surface, it can be evenly dispersed in the coating. On the one hand, a maze effect is formed to inhibit the occurrence of corrosion; on the other hand, the fillers are dispersed and contacted with each other, which is conducive to forming an effective heat conduction channel.
[0064] Figure 3 The thermal conductivity of the epoxy composite coating made of the composite functional filler in Example 1 of the present invention and the coating made of hexagonal boron nitride are compared. The surface modification of hexagonal boron nitride will not destroy the thermal conductivity of the coating. On the contrary, due to the effective dispersion of boron nitride, the thermal conductivity of the coating can be promoted.
[0065] Figure 4 This is a comparison of the epoxy composite coating made of the composite functional filler in Example 1 of the present invention and the coating made of ordinary hexagonal boron nitride after salt spray corrosion. Compared with the latter, the functional filler prepared based on Example 1 has better corrosion resistance, and the gallic acid in the system can form a chelating effect with the generated iron ions, thereby inhibiting the occurrence of corrosion.
[0066] Therefore, the modified silica sol is obtained by condensing the carboxyl group on the gallic acid with the hydroxyl group of the silica sol, and the modified silica sol is mixed and dispersed with an ethanol dispersion of hexagonal boron nitride, heated and dried, ground, dispersed and sieved to obtain the composite functional filler with both thermal conductivity and anti-corrosion effects of the present invention; the composite coating is further added to a polymer resin to prepare a composite coating for application in the field of coating protection. The prepared composite coating has a rust conversion effect on the basis of thermal conductivity, improves the corrosion resistance of the coating, and has great application prospects.
Claims
1. A composite functional filler having both thermal conductivity and anti-corrosion effects, characterized in that: The composite functional filler is based on boron nitride, and its surface is physically coated and modified by silica sol modified by a rust conversion agent.
2. The composite functional filler according to claim 1, characterized in that: The rust converting agent is gallic acid, and the boron nitride is hexagonal boron nitride.
3. A method for preparing the composite functional filler according to claim 1, characterized in that: The following steps are involved: (1) dissolving gallic acid in an ethanol solvent, then adding the gallic acid to the silica sol, and after being evenly dispersed, adding a catalyst to carry out a condensation esterification reaction, stirring at a speed of 400 to 800 rpm, heating to 50 to 70° C., and reacting for 4 to 8 hours to obtain an intermediate product I; (2) first adding a wetting dispersant to anhydrous ethanol, then adding hexagonal boron nitride powder, and ultrasonically dispersing for 4 to 6 hours to fully disperse it, thereby obtaining an intermediate product II; (3) mixing the intermediate product I with the intermediate product II, and stirring at a rotation speed of 200 to 1000 rpm at room temperature for 0.5 to 5 hours to obtain a mixture; (4) The mixture is placed in a rotary evaporator, heated to 40°C to 60°C at 0.05 to 0.2 atmospheres, reacted for 0.5 to 2 hours to remove the solvent, and the obtained product is dispersed by ball milling and sieved to obtain a composite functional filler with both thermal conductivity and anti-corrosion effects.
4. The method according to claim 3, characterized in that: In step (1), the concentration of gallic acid in ethanol is 0.5-5 g / ml; the silica sol has a solid content of 30%, a particle size of 10-20 nm, and a pH value of 7-10.
5. The method according to claim 3, characterized in that: In step (1), the catalyst is dimethylamino arsenic.
6. The method according to claim 3, characterized in that: In step (2), the wetting and dispersing agent is an anionic wetting and dispersing agent, such as sulfate ester salt, sulfonate ester salt, sodium oleate, carboxylate, etc.
7. The method according to claim 3, characterized in that: In step (2), the particle size of the hexagonal boron nitride ranges from 5 to 30 microns.
8. The method according to claim 3, characterized in that: In step (2), the concentration of boron nitride dispersed in anhydrous ethanol is 25-100 g / l, the frequency of ultrasonic dispersion is 40 kHz, and the power range is 50-900 W.
9. The method according to claim 3, characterized in that: In step (3), the mass ratio of intermediate product I to intermediate product II is 100:1 to 10:
1.
10. Use of the composite functional filler according to claim 1 in the field of coating protection.